Newly fault-tolerant indirect vector control for traction inverter - Sara Zerdani; Mohamed Larbi Elhafyani; Hicham Fadil; Smail Zouggar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The traction inverter is a crucial power device in the electric vehicle’s powertrain, and its failure is intolerable as it would considerably compromise the system’s safety. For more reliable driving, installing a traction inverter that is sufficiently resistant to electrical failure is inherent. Due to its compact size and the small number of switches incorporated in three-phase four-switch inverter, this modular topology was used to compensate for the open switch’s failure. However, it is known to have manifold weaknesses mainly distinguished in the low-frequency region. This paper introduces a new fault-tolerant indirect control that handles the IGBT’s failure constituting the traction inverter. The fault compensator is designed first based on the Proportional Integral regulator combined with the notch filter to mitigate the current imbalance and restore the DC voltage equilibrium.Furthermore, to conceive a comprehensive fault-tolerant control, there must therefore contain an accurate fault detector. In this regard, an uncomplicated fault diagnosis method based on the current spectral analysis has been performed. The effectiveness of the submitted controller was validated by simulation using Matlab.